The functioning of yacht charter companies in Croatia and Poland – a comparative perspective - Łapko, Aleksandra; Lučić, Lovorko (Funkcjonowanie polskich i chorwackich przedsiębiorstw czarterujących jachty – porównanie, 2019)
The article presents and compares the functioning of the yacht charter market in Croatia and Poland. Croatia is the leading European tourist destination in which nautical tourism is one of the leading branches of the economy. There are very restrictive regulations regarding the conduct of charter activities. In Poland the dynamic development of nautical tourism has been observed for a dozen or so years, but it is only now taking on significance for the economy. There are no special regulations relating to the operation of yacht chartering companies. The solutions applied in Croatia were treated as an example of good practices on the basis of which recommendations for Poland were formulated. The article presents the concepts of yacht charter, the regulations regarding charter companies, data on the charter offer range available in both countries and the conclusions. Research is based on the method of literature analysis, online resources and observation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 197-206
Keywords: nautical tourism; yacht charter companies; management of tourism development; turystyka żeglarska; czartery jachtów; zarządzanie rozwojem turystyki żeglarskiej